Sensing properties of Ni-doped boron nitride nanotube to SF6 decomposed components: A DFT study - Shoumiao Pi; Xiaoxing Zhang; Dachang Chen; Ju Tang (AIP Advances, 2019)
In this paper, the sensing property of Ni-BNNT to SO2, SOF2 and SO2F2 were investigated based on the DFT method to explore its potential as a chemical gas sensor. Our results show that Ni-doping could significant deform the electronic behavior of the BNNT, reducing its bandgap largely, from 3.712 eV to 0.601 eV. Ni-BNNT behaves strong chemisorption upon SO2 molecule with adsorption energy of -0.864 eV, while weak physisorption upon SOF2 and SO2F2 molecules with adsorption energy of -0.522 and -0.223 eV. The DOS analysis suggests the strong electron hybridization in SO2 system, while weak orbital interaction in the SOF2 and SO2F2 systems. Upon SO2, the Ni-BNNT could be a promising sensors for sensitive detection while it is unsuitable for detecting SOF2 or SO2F2 due to the weak interaction and extremely short recovery time. This work provides a first insight into the application of Ni-BNNT for detecting SF6 decomposed components, which would be beneficial for effectively evaluating the operation status of SF6 insulated devices.